Yield of Malignant Pleural Effusion for Detection of Oncogenic Driver Mutations in Lung Adenocarcinoma. Issue 2 (April 2019) - DeMaio, Andrew; Clarke, Jeffrey M.; Dash, Rajesh; Sebastian, Siby; Wahidi, Momen M.; Shofer, Scott L.; Cheng, George Z.; Li, Xuechan; Wang, Xiaofei; Mahmood, Kamran
Abstract : Background: Pleural fluid can be used to assess targetable mutations in patients with lung adenocarcinoma. The primary objective of this study was to assess the yield of pleural fluid cytology for targetable oncogenic mutations ( EGFR, KRAS, BRAF, ALK, and ROS1 gene rearrangements). We also assessed pleural fluid volume necessary for molecular testing. Methods: Retrospective review was performed of 134 consecutive patients with lung adenocarcinoma associated malignant pleural effusions. EGFR and KRAS testing was done using PCR amplification followed by DNA sequencing, or next generation sequencing in more recent cases that included BRAF assessment. Fluorescence in situ hybridization employing break-apart probes was used to test for ALK and ROS1 rearrangements. Results: Mutation analysis on pleural fluid cell-block was performed on 56 patients. It was adequate for complete analysis ordered including EGFR, KRAS, BRAF, ALK, and ROS1 rearrangements on 40 (71.4%) samples. For individual mutations, EGFR testing was possible in 38 of 49 (77.6%); KRAS 22 of 28 (78.6%); BRAF 10 of 13 (76.9%), ALK gene rearrangement 42 of 51 (82.4%) and ROS1 gene rearrangement in 21 of 28 (75%) pleural fluid specimens. The analysis was satisfactory in 13 of 19 (68.4%) samples with ⩽100 mL versus 27 of 37 (72.9%) with >100 mL of fluid tested ( P -value=0.7). Conclusion: Genetic mutation analysis can be performed on malignant pleural effusions secondary to lung adenocarcinoma, independent of fluid volume.